Feline heart disease: prevalance, risk factors, and staging - Khor, Kuan Hua; Ahmad, Zakaria; Abdullah, Rasedee @ Mat (Veterinary Association Malaysia, 2018)
Heart disease in cats can lead to congestive heart failure if untreated. This retrospective study on feline heart disease was conducted at University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) using data collected for the period of 2013 to 2015. In this study, the prevalence of cats with heart disease was 1% (n=155/15,493) and the cases diagnosed were on the increase during that period. The mean age of feline heart disease patients were 5.2 years with age range of 2-month to 20-year-old. Male (57%) were more often diagnosed with heart disease than female (43%) cats. The two most common breeds of cats presented with heart diseases were Domestic Shorthair (54%) and Persian (26%). Ten of 155 cat patients diagnosed with heart diseases were asymptomatic while the rest were presented with various clinical signs predominantly of congestive heart failure. Most cats were diagnosed with acquired heart diseases (98%) with hypertrophic cardiomyopathy as the most prevalent (51%), followed by dilated cardiomyopathy (19%), restrictive cardiomyopathy (15%), and various other types of heart disease (pericardial effusion, aortic insufficiency, heart base tumor, and feline heartworm disease) (6%), and myocarditis (7%). Congenital heart diseases (2%) diagnosed in the cats were atrial and ventricular septal defects. Based on staging using a modified New York Heart Association Classification, the majority of the feline heart patients were of Class II (n=52) and III (n=67), followed by Class IV (n=26), and Class I (n=10). Echocardiography remains the best diagnostic tool for the diagnosis of heart disease in cats.